Dinámica familiar campesina durante la cuarentena en el Distrito de San Juan de Jarpa - Rojas Carhuamaca, Wilmer (2022)
The family dynamics in its interactions and structure is conditioned by the type of organization and the internal rules that regulate the performance of tasks by each member. In the field of peasant families, this configuration of roles and functions is even more marked. In this case, the objective was formulated to describe the peasant family dynamics during the quarantine in the district of San Juan de Jarpa in the year 2020. The study is then quantitative, of a descriptive level, with a sample of 72 families, to which They applied a questionnaire and an in-depth interview guide. The following result was obtained: 62% of families consider that communication between household members was adequate and developed steadily, since interest, active listening and respect for the other's opinion prevailed; likewise, 67% of the families mentioned that family affectivity developed adequately and constantly, presenting itself through the expression of feelings; finally, 55% of the families report that the peasant family role was adequate and developed steadily, since the members of the household were able to distribute internal activities effectively. Through the results, the conclusion was obtained, where the peasant family dynamics during the quarantine is adequate, responding to the forms of communication, affectivity and role development.